Effect of supplemental vitamin D on prostate volume in patients with symptomatic benign enlargement of prostate - Mortuza, Md Ishtiaqul Haque; Alam, AKM Khurshidul; Arif, Taslim; Haider, Mominul; Khan, Sarforaj Ali (Bangladesh Journal of Urology, 2025)
Background: Vitamin D is essential for the normal function of multiple organs of the body. Studies have suggested there is an association between vitamin D deficiency and benign enlargement of prostate (BEP). Objective: To evaluate the effect of oral vitamin D supplementation on prostate volume in patients with lower urinary tract symptoms (LUTS) due to BEP. Methods: This was a quasi-experimental study conducted from November 2020 to February 2022 in Urology OPD, Bangabandhu Sheikh Mujib Medical University, Dhaka. After evaluation of 132 patients, 15 were excluded for not meeting the criteria. Total 117 patients were enrolled in this study but with a drop out of 8 patients finally 109 male patients having LUTS due to BEP were purposively selected for the study. Patients received treatment with testosterone, 5-alpha-reductase inhibitors, or any other hormone therapy (in previous 6 months), having prostate or bladder cancer or Serum PSA values of >4 ng/ml were excluded from the study. Face-to-face interview and medical record review were used as the techniques for data collection. Data were collected in an interviewer administered questionnaire. A check list was also used containing International Prostate Symptom Score (IPSS) and investigation reports for collecting data regarding LUTS, prostate volume, serum vitamin D level, serum creatinine, serum PSA and urinary flow rate. After initial assessment patients with vitamin D insufficiency or deficiency were prescribed alpha-1 blocker (Tamsulosin) and oral supplementation tablet containing calcium 600mg with Vitamin D 400IU twice daily for 12 weeks. In the follow up visit after 12 weeks, IPSS score, Prostate volume, Serum 25(OH) D level of the patients were assessed again. Then the effect of the supplementation was evaluated. Results: The mean (±SD) age of the patients was 61.9 ±5.7 years. Before oral vitamin D supplementation, 48 (44.0%) had deficient while 61 (66.0%) had insufficient serum 25(OH) D. The mean prostate volume of the patients was significantly lowered after oral vitamin D supplementation (29.0 ±3.2 mL) compared to before supplementation (33.8 ±3.4 mL) (p<0.001). The median IPSS of the patients was also significantly lowered after oral vitamin D supplementation (10.0) compared to before supplementation (14.0) (p<0.001). Before oral vitamin D supplementation, only 10 (9.2%) were mildly symptomatic and 99 (90.8%) were moderately symptomatic while after oral vitamin D supplementation, 28 (25.7%) were mildly symptomatic while 81 (74.3%) were moderately symptomatic (p=0.002). No significant statistical difference was observed between the patients with or without comorbidities regarding prostate volume before and after oral vitamin D supplementation (p>0.05). Prostate volume significantly reduced in normal, overweight, and obese patients after oral vitamin D supplementation (p<0.001). Conclusion: Oral vitamin D supplementation significantly reduced prostate volume symptom status, co-morbidity, and BMI in patients with lower urinary tract symptoms due to BEP. Bangladesh J. Urol. 2024; 27(1): 11-15